Mitogenomics of the endangered Mediterranean monk seal (Monachus monachus) reveals dramatic loss of diversity and supports historical gene-flow between Atlantic and eastern Mediterranean populations. Issue 4 (28th August 2020) - Rey-Iglesia, Alba; Gaubert, Philippe; Espregueira Themudo, Gonçalo; Pires, Rosa; de la Fuente, Constanza; Freitas, Luís; Aguilar, Alex; Borrell, Asunción; Krakhmalnaya, Tatiana; Vasconcelos, Raquel; Campos, Paula F
Abstract: The Mediterranean monk seal Monachus monachus is one of the most threatened marine mammals, with only 600–700 individuals restricted to three populations off the coast of Western Sahara and Madeira (North Atlantic) and between Greece and Turkey (eastern Mediterranean). Its original range was from the Black Sea (eastern Mediterranean) to Gambia (western African coast), but was drastically reduced by commercial hunting and human persecution since the early stages of marine exploitation. We here analyse 42 mitogenomes of Mediterranean monk seals, from across their present and historical geographic ranges to assess the species population dynamics over time. Our data show a decrease in genetic diversity in the last 200 years. Extant individuals presented an almost four-fold reduction in genetic diversity when compared to historical specimens. We also detect, for the first time, a clear segregation between the two North Atlantic populations, Madeira and Cabo Blanco, regardless of their geographical proximity. Moreover, we show the presence of historical gene-flow between the two water basins, the Atlantic Ocean and the Mediterranean Sea, and the presence of at least one extinct maternal lineage in the Mediterranean. Our work demonstrates the advantages of using full mitogenomes in phylogeographic and conservation genomic studies of threatened species.